Single‐dose tranexamic acid in advanced ovarian cancer surgery reduces blood loss and transfusions: double‐blind placebo‐controlled randomized multicenter study. (25th February 2014) - Lundin, Evelyn S.; Johansson, Torsten; Zachrisson, Helene; Leandersson, Ulf; Bäckman, Fatma; Falknäs, Laila; Kjølhede, Preben
Abstract Objective To determine whether single‐dose tranexamic acid given intravenously immediately before surgery for presumed advanced ovarian cancer reduces perioperative blood loss and blood transfusions. Design A randomized double‐blind, placebo‐controlled multicenter study. Setting Two university hospitals and two central hospitals in the southeast health region of Sweden. Population One hundred women with presumed advanced ovarian cancer scheduled for radical debulking surgery between March 2008 and May 2012 who complied with inclusion/exclusion criteria were randomized; 50 were allocated to receive tranexamic acid and 50 to receive placebo. Analysis was performed according to intention‐to‐treat principles. Methods The volume of tranexamic acid (15 mg/kg body weight, 100 mg/mL tranexamic acid) or the same volume of placebo (0.9% NaCl) was added to a 100‐mL saline solution plastic bag. The study medication was given immediately before the start of surgery. Data were analyzed by means of non‐parametric statistics and multivariate models adjusted for confounding factors. Main outcome measures Blood loss and red blood cell transfusions. Results The total blood loss volume and transfusion rate were significantly lower in the tranexamic acid group compared with the placebo group. Median total blood loss was 520 and 730 mL, respectively (p = 0.03). Fifteen (30%) and 22 (44%), respectively received transfusions (odds ratio 0.44; upper 95% CI 0.97; p = 0.02). Conclusion A single dose of tranexamic acid given immediately before surgery reduces blood loss and transfusion rates significantly in advanced ovarian cancer surgery. Tranexamic acid may be recommended as standard prophylactic treatment in advanced ovarian cancer surgery.